The Year of 1938, and the Politics of Homogenization in Europe on the Eve of World War Two - V. V. Vasilenko (Tractus Aevorum, 2019)
The author gives an overview of the conference “‘1938’ and the Politics of Homogenization. Protecting the Nation in Europe on the Eve of World War II” which took place in Prague in October 2018.